Image based autonomous indoor parallel parking assist on omni-directional vehicle (ODV) - Edwind, Liaw Yee Kang (2016)
Nowadays, Omni-Directional Vehicle (ODV) has been widely used in many fields to perform autonomous missions. Equipped with sensors and pre-programmed navigation systems, ODV can be designed to replace humans in performing dangerous tasks in various fields such as planet exploration and industrial applications. In this research, the implementation of image processing techniques on vehicle’s control has been proposed to develop autonomous indoor parallel parking assist on ODV. The image processing algorithm is first developed using Visual Studio C++ and OpenCV. The electrical circuit of the ODV has been designed and installed. Then, the developed image processing algorithm is integrated with the microcontroller of the ODV, Arduino Mega 2560. After that, an experimental environment has been constructed and set-up to test and analyze the performance of the developed system. As a result, the proposed and developed system is able to work in indoor lighting range.